S-GIS: DIGITAZING SKIN DISEASE SPREAD IN LAMPUNG PROVINCE INDONESIA - Rahmalia Syahputri; Muhammad Said Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Skin disease is a common disease whether in urban orrural area. Various types are listed in this category. Someof them are easily transmitted and turn into epidemic. Tohelp the health department or other parties to map thespread of the diseases as well as to broadcast theinformation easily to the citizen, thus it is important todevelop a system that able to provide data based ongograpfical. Furthermore, the data should be easily to beaccesed.To enable related parties to be able to collect,store, and analyze the spread of skin disease particularlyin Lampung Province Indonesia, a geographicalinformation system has been developed. In addition, thissystem acts as a monitoring tool for Government orAgencies that responsible for the health issues inLampung and Indonesia.KEY WORDS: geographic information system, skindiseases spread, Lampung Province.